2001
DOI: 10.1002/etc.5620200722
|View full text |Cite
|
Sign up to set email alerts
|

Fate and effects of esfenvalerate in agricultural ponds

Abstract: The fate of esfenvalerate was investigated by sampling and chemical analysis after spraying of an artificial pond (25 g a.i./ha) and in the laboratory with [14C]esfenvalerate by trapping of 14CO2 and fractionation of the sediment. The effects were investigated on pelagic communities in enclosures in a natural lake and in the laboratory on surface (Cymatia coleoptrata) and sediment (Chironomus riparius) insects. The latter were used in sediment-plus-water and in water-only tests, measuring effects on emergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Reduced adult emergence of mayflies was observed 29 days after one-hour exposures to 0.01 µg/L esfenvalerate, a concentration three orders of magnitude lower than concentrations determined to result in acute mortality in this species (Beketov & Liess, 2005). Interestingly, the emergence of Chironomus riparius larvae from artificial ponds was stimulated at low esfenvalerate concentrations (0.1 and 0.2 µg/L), but was delayed by concentrations of 0.8 µg/L and greater (Samsøe-Petersen et al, 2001). However, given that the life cycles of semi-aquatic insects are finely attuned to seasonal and environmental cues, improperly timed emergence can result in new adults emerging into inhospitable climatic conditions.…”
Section: Effects On Aquatic Insect Emergencementioning
confidence: 87%
See 2 more Smart Citations
“…Reduced adult emergence of mayflies was observed 29 days after one-hour exposures to 0.01 µg/L esfenvalerate, a concentration three orders of magnitude lower than concentrations determined to result in acute mortality in this species (Beketov & Liess, 2005). Interestingly, the emergence of Chironomus riparius larvae from artificial ponds was stimulated at low esfenvalerate concentrations (0.1 and 0.2 µg/L), but was delayed by concentrations of 0.8 µg/L and greater (Samsøe-Petersen et al, 2001). However, given that the life cycles of semi-aquatic insects are finely attuned to seasonal and environmental cues, improperly timed emergence can result in new adults emerging into inhospitable climatic conditions.…”
Section: Effects On Aquatic Insect Emergencementioning
confidence: 87%
“…This disruption of behavioral homeostasis can alter feeding rates, cause loss of coordination and paralysis, or stimulate hyperactivity that may increase exposure to predators, both of which can have ecologically-relevant consequences. Surface insects were observed to be susceptible to pyrethroid over-spray, exhibiting a rapid loss of coordination and paralysis in response to esfenvalerate only a few hours after application (Samsøe-Petersen et al, 2001). Following sublethal aquatic exposures to cypermethrin, cyfluthrin, and deltamethrin, red swamp crayfish exhibited similar responses (Morolli et al, 2006).…”
Section: Effects Of Pyrethroids On Nontarget Aquatic Invertebrates 8mentioning
confidence: 99%
See 1 more Smart Citation
“…When esfenvalerate was applied as 0.1% acetonitrile solution in darkness, 14 CO 2 finally amounted to 21.8% of the applied 14 C. More formation of CO 2 as compared with the illuminated studies was accounted for by predominantly microbial processes in the presence of sediment. Samsfe-Petersen et al 26) have reported mineralization of less than 5% in the same period from [phenoxyphenyl-14 C]esfenvalerate in darkness when applied to a Danish pond water-sediment system at 5 and 98 ppb. This difference was likely to stem from the lower temperature (15°C) in their study.…”
Section: Degradation In the Water-sediment Systemmentioning
confidence: 95%
“…These factors are likely to mitigate the contribution of a runoff application to the effects of a combined spray and runoff application. Particularly in drift simulating applications to stagnant waters, clear concentration gradients of insecticides can be found in the first hours posttreatment (Muir et al, 1992;Fairchild and Eidt, 1993;Crum and Brock, 1994;Farmer et al, 1995;Samsøe-Petersen et al, 2001). Shortly after drift applications, most of the active ingredient is then found in the superficial water layer.…”
Section: Application Methods and Pesticide Behaviourmentioning
confidence: 99%